Microscopical and molecular investigation of Ichthyophthirius multifiliis from fish in Mosul city, Iraq - Esraa A. Altaie; Nadia N. Alhayali (Iraqi Journal of Veterinary Sciences)
The ectoparasite Ichthyophthirius multifiliis (I. multifiliis) is one of the most common external ciliate protozoa that infest freshwater fish and causes white spot disease, negatively affecting fish productivity. Two hundred of five species of fish (25 Luciobarbus xanthopterus, 30 Chondrostoma regium, 35 Mesopotamichthys sharpeyi, 54 Cyprinus carpio, and 56 Arabibarbus grypus) were collected from Mosul city markets from Aug. 2023 to Feb. 2024. Microscopically, fish were infected with the ectoparasite I. multifiliis (13/200) 6.5% total infestation rate by wet smears from skin, gills, and fins and based on the morphological features; the ectoparasite were pear-shaped, 0.03 - 1 mm with large horseshoe nuclei. Molecular phylogenetic analysis conducted with 18S rRNA gene confirming species identification of one positive isolate out of 13 belonging to the ectoparasite I. multifiliis under the accession number PQ012981 and according to the genetic tree analysis of I. multifiliis showed 100% match with each of the United States isolates for the same species and under the accession numbers KJ690571, KJ690572, KJ690570, KJ690568, KJ690567, KJ690566 and KJ690565 and isolates OM865867 in India and OM302501 in China. In contrast, it showed a 99.93% match with isolates MN372056 in the Philippines and ON797789 and ON797786 in China, as recorded in the GenBank. The current study is considered the first record of Ichthyophthirius multifiliis at the molecular level in Mosul City, Iraq.